Modelling of an OBS profile across Storfjorden, Svalbard - Hauge, Brede Engum (The University of Bergen, 2018)
In this thesis, seismograms from eight Ocean Bottom Seismometers (OBS) have been processed, interpreted and used to obtain a 2D velocity model of a crustal transect across Storfjorden south of Svalbard through forward/inverse modelling. The aim of the study is to increase the understanding of an assumed Caledonian suture in the area, as well as recent earthquake activity. The modelling reveals a maximum Moho depth in the area predicted to be intersected by the suture. Together with a dipping down-to-west trend of the crust and mantle, this indicates the presence of an old subduction zone, supporting earlier research on the topic. From magnetic and gravitational maps of the area this suture seems to follow the trend of the Billefjorden Fault zone. Recent seismic activity in the area is for the most part gathered in a large southwestern and small north-eastern cluster. The clusters follow a SW-NE trend across Storfjorden along a proposed Tertiary shear zone and are located at the intersection between this and several major north-south oriented structures. These are mainly the suture and possible southward extensions of the Billefjorden Fault Zone and Lomfjorden Fault Zone in the south-west, and near the intersection with a possible southern extension of the Storfjorden Fault Zone in the north-east. Masteroppgave i geovitenskap GEOV399